Evaluation of contribution of salinity, irradiance, and nutrient deficiency into the yield of cells and -carotene accumulation in the culture of Dunaliella salina (Chlorophyta) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The purpose of the study was to evaluate the contribution of salinity, irradiance, nitrate and phosphate, and their interactions into the yield of cell number and -carotene accumulation in Dunaliella salina. To avoid confounding of the effects of factors-conditions by the depletion of factors-resources, the alga was grown in fed-batch culture. In the level ranges of the experimental factors (irradiance 2–8 klx, salinity 1–4 M NaCl, KNO3 0–80 mg L-1, K2HPO4 0–10 mg L-1), nitrate and phosphate influenced the productivity of culture by cell number and -carotene accumulation more strongly than salinity and irradiance. Effects of salinity and irradiance depended on nutrients and their pre-supply to the inoculum. Total effect size 2 of nutrients on cell yield comprised 0,59 for non-starved and 0,43 for starved inoculum, whereas total effect size of factors-conditions – 0,10 and 0,12 correspondingly. As to cellular -carotene content, total effect size of nutrients on the cells grown from non-starved and starved inoculum was 0,71 and 0,58, and of factors conditions – 0,8 and 0,5 correspondingly. Remained variances of cell yield and -carotene content were attributed to the interactions of salinity and irradiance with the nutrients. The combination of high values of salinity and irradiance exerted its own, unconfounded by depletion of nutrients, but lower influence on -carotene accumulation. The highest -carotene content of 53 pg per cell was observed in the culture grown from the starved inoculum at the deficiency of phosphorus. Combination of high salinity and irradiance values yielded 17 pg of -carotene per cell compared to about 5 pg under the optimal culture conditions. Controll nutrient supply would be the most powerful tool for biosynthesis control in D. salina culture.
Keywords: nitrate, phosphate, microalga, cultivation methodology.